Porous graphene and graphenylene nanotubes: Electronic structure and strain effects - Fabris, Guilherme S.L. [UNESP]; Junkermeier, Chad E.; Paupitz, Ricardo [UNESP] (Elsevier, 2017)
The unusual and unique mechanical and electronic properties of nanostructured carbon materials make them useful in the construction of nanodevices. We investigate a new class of structures, called porous nanotubes, which are constructed from two recently synthesized two-dimensional materials, namely the porous graphene (PG) and the two-dimensional carbon allotrope known as graphenylene, also known as Biphenylene Carbon (BPC). We investigate this class of quasi-one-dimensional materials using the density functional tight-binding (DFTB) method to optimize geometries and to calculate electronic structure features of these systems. For each type of porous nanotube, calculations were performed on tubes with several diameters and chiralities. Our results show that the PG nanotubes have a wide band-gap, ∼3.3eV, and the graphenylene nanotubes have a semiconductor behavior with a band gap around 0.7 eV. They also show that as the diameter of a PG nanotube increases the band-gap decreases, while for the graphenylene nanotube the band gap increases. In both cases, the observed gap variation with increasing diameter is towards the value found for the respective two-dimensional membrane. Calculations on axially strained porous nanotubes show a decrease on the band gap of ∼10% for some chiralities of the PG nanotube and an increase for the graphenylene nanotubes gap that can become as high as 100%. These results are in contrast with the expected behavior for carbon nanotubes, which show a linear dependence between gap opening and applied strain under similar conditions.
Keywords: Carbon nanotubes; Graphenylene; Porous graphene; Porous nanotubes; Simulation; Strain effects